Reality mining : using big data to engineer a better world - Eagle, Nathan; Greene, Kate, 1979- (The MIT Press, 2014)
In this book, the authors explore the positive potential of big data, showing the ways in which the analysis of big data ("reality mining") can be used to improve human systems as varied as political polling and disease tracking, while considering user privacy. They describe reality mining at five different levels: the individual, the neighborhood and organization, the city, the nation, and the world. For each level, they offer a nontechnical explanation of data collection methods and describe applications and systems that have been or could be built. These include a mobile app that helps smokers quit smoking; a workplace "knowledge system"; the use of GPS, Wi-Fi, and mobile phone data to manage and predict traffic flows; and the analysis of social media to track the spread of disease. The authors argue that big data, used respectfully and responsibly, can help people live better, healthier, and happier lives. -- Edited summary from book.
Keywords: Data mining.; Big data.; Computer networks -- Social aspects.; Information science -- Social aspects.; Information science -- Statistical methods.; elektronické knihy; electronic books